Odpowiedzi

2010-03-28T14:11:33+02:00
A) 3x-5=4+2x
x=9
b) -5+10=-2x-8
12x=-3 |:12
x=-0,25
c)-5x-17=-9x+3
4x=20 |:4
x=5
d)7x+14=5x-22
2x=-36 |:2
x=-18
e)2x-4+5x=x+2
6x=6 |:6
x=1
f)-3+2x-6=3-4x
6x=12 |:6
x=2
g)7x+2=5+3x+9
4x=12 |:4
x=3
h)-5x+12+x=2x-12
6x=-24 |:6
x=-6
i)2(x-3)+3(4-x)=5
2x-6+12-3x=5
x=1
j)3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
x=2
k)2(x+4)-5(x+3)=2
2x+8-5x-15=2
-9=3x |:3
x=-3
l)-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x=0 |:
x=0
2010-03-28T14:33:41+02:00
A) 3x-5=4+2x |+5
3x=9+2x |-2x
x=9
b) -5+10=-2x-8
5=-2x-8 |+8
13=-2x | * (-1)
-13=2x
x=-6.5
c)-5x-17=-9x+3 |+9x
4x-17=3 |+17
4x=20 |/4
x=5
d)7x+14=5x-22 |+22
7x+36=5x |-7x
36=-2x |/2
x=18
e) 2x-4+5x=x+2
7x-4=x+2 |+4
7x=x+6 |-x
6x=6
x=1
f)-3+2x-6=3-4x
-9+2x=3-4x |+4x
-9+6x=3 |+9
6x=12 |/6
x=2
g)7x+2=5+3x+9
7x+2=14+3x |-3x
4x+2=14 |-2
4x=12
x=3
h)-5x+12+x=2x-12
-4x+12=2x-12 |-12
-4x=2x-24 |-2x
-6x=-24 |/6
x=4
i) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
-x+6=5 |-6
-x=-1
x=1
j)3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
-x-2=-4 |+2
-x=-2
x=2
k)2(x+4)-5(x+3)=2
2x+8-5x-15=2
-3x-7=2 |+7
-3x=9 |/(-3)
x=-3
l)-2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x+6=-6 |-6
6x=-12 |/6
x=-6

licze na naj